Hypoxia-inducible factor HIF-1? modulates drugs resistance in colon cancer cells (2018)
Introduction: Drug resistance mechanisms may be associated with decreased cell death and its induction may depend on the response to oxidative stress caused by hypoxia. The correlation between hypoxia-inducible factor HIF-1?, the number of reactive oxygen species and their effect on cell survival has not yet been evaluated. Objective: The purpose of this study was to evaluate the effect of HIF-1? activity and reactive oxygen species (ROS) accumulation in apoptosis of colon cancer cells. Materials and methods: HT29 colon cancer cells were treated with Cobalt(II) chloride (CoCl2) or doxorubicin and the activity of HIF-1? was determined by ELISA assay. ROS were determined using fluorescence probe carboxy-H2DFFDA. Apoptosis was assessed by caspase-3 activation analysis, and PUMA and BAX mRNA levels by qRT-PCR. The reduction of the antiapoptotic effect due to hypoxia was attenuated by use of the endonuclease APE-1 (E3330) inhibitor. The endonuclease E3330 APE-1 inhibitor allowed evaluating the effect of ROS generated by doxorubicin and CoCl2 on apoptosis. Results: Chemical hypoxia in combination with doxorubicin is an oxidative stressor in HT29 cells and induces a reduction in the apoptotic process in a time-dependent manner. Conclusion: Resistance to hypoxia and doxorubicin-mediated cell death could be controlled by a mechanism related to the activity of HIF-1? and the amount of reactive oxygen species generated. © 2018, Universidad Nacional de Colombia. All rights reserved.